A Hybrid Data Level Approach for Improving Classification Performance in Imbalanced Dataset - ประจวบศุภกิจ วันทนี (Progress in Applied Science and Technology, 2018)
The imbalanced problem occurs when the number of instance in the one class sharply outnumber another class. The classification on imbalanced data always brings about problems because the traditional classifiers tend to predict well on the majority class while the prediction based on the minority class is poor. Therefore, the aim of this research is to propose the hybrid data level approaches in order to improve the classification performance based on the two-class imbalanced dataset. This research introduces a new approach that combines the clustering approach of k-means algorithm and over-sampling techniques namely Clustering Switching Method for Sampling Imbalanced Data or ClusIM. The research’s result shows that ClusIM has higher F-measure and G-mean results than the other methods especially on majority classes that ClusIM obtains the F-measure and the G-mean values about 90% on all dataset. Moreover, ClusIM reduced the overlap and imbalanced ratio between classes to get good performance.